ANALYSIS OF CALCULATION IN Mudharabah TO INCREASE REVENUE TRADERS IN BMT of ATI BENING GROBOGAN DISTRICT - Tida, Khusnamah; Kholisoh, Dr. Luluk; Nawarcono, SE., MM, Winanto (Accounting, 2010)
The existence of an existing conventional bank interest in the system prioritizes operasiolnalnya, while the Islamic Bank are not familiar with the term of interest but which is the term used for the results. Banking with sharing system designed terbinanya for unity in the risks and share the results of operations between the owner of the funds that keep their money in the bank, with the bank as manager funds and also the people who need funds that can be existed as borrower or the fund manager. With financing coupled with the guidance capital management and business to business productivity help to improve which in turn will affect the increased revenue traders small. This is the basis for the author to take the title